A+ certification - Moulton, Pete 1944- (Prentice Hall PTR, 2000)
Master PC troubleshooting and repair, pass the industry-leading A+ certification exam - and have fun doing it! A+ Certification gives you all the rigorous exam preparation you need - without the pain! You'll find easy-to-understand photos, real-world anecdotes from the trenches, plenty of A+ sample questions and more! This book covers every exam objective.